2020
DOI: 10.1002/ptr.6799
|View full text |Cite
|
Sign up to set email alerts
|

Schisandra chinensis ameliorates depressive‐like behaviors by regulating microbiota‐gut‐brain axis via its anti‐inflammation activity

Abstract: The present study aimed to examine the antidepressant actions of the composition fractions of Schisandra chinensis using LPS‐induced mice. Animals were treated with total extracts (SCE), lignans (SCL), polysaccharides (SCPS), and essential oil (SCVO), and then subjected to behavioral tests. The forced swimming test (FST) and tail suspension test (TST) were used as predictive animal models of antidepressant activity. Total extracts and lignans significantly decreased the duration of immobility in FST and TST. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In this study, the SJE treated group, especially the low-dose group, significantly alleviated the DSS-induced depressive/anxious behavior. Some plant extracts, such as Schisandra Chinensis ( 30 ), and okra seeds ( 4 ) have also shown similar effects and suggested that the major bioactive substances were polyphenols, flavonoids, lignans, saponins and other small molecules. SJE also contains a variety of bioactive substances, such as brown algae polyphenols and lignans, which have potential therapeutical effects on the DSS-induced depressive behavior in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the SJE treated group, especially the low-dose group, significantly alleviated the DSS-induced depressive/anxious behavior. Some plant extracts, such as Schisandra Chinensis ( 30 ), and okra seeds ( 4 ) have also shown similar effects and suggested that the major bioactive substances were polyphenols, flavonoids, lignans, saponins and other small molecules. SJE also contains a variety of bioactive substances, such as brown algae polyphenols and lignans, which have potential therapeutical effects on the DSS-induced depressive behavior in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Schisandra chinensis [311], helicid [312], panaxynol [313], and safflower extract [314] regulated various factors in the NF-κB and toll-like receptor 4-nucleotide-binding and oligomerization domain-like receptor 3 (NLRP3) signaling pathways. The honey fungus Armillaria mellea [315] reduced TNF-α and IL-1β [316].…”
Section: Plantsmentioning
confidence: 99%
“…Radix polygalae increased autophagy and reduced neuroinflammation [317]. Schisandra chinensis [311], Cistanche tubulosa [318], and Sophora alopecuroides [319] promoted diverse intestinal microbiome.…”
Section: Plantsmentioning
confidence: 99%
“…NF-κB activation results in tissue changes characteristic of inflammation. Schisandra chinensis extract (SCE) and Schisandra chinensis lignans (SCL) can greatly inhibit the TLR4/NF-κB/IKKα signaling pathway, and indicate that Schisandra chinensis ameliorates depressive-like behaviors by regulating microbiota-gut-brain axis via its anti-inflammation activity ( 173 ). Astilbe Chinensis ethanol extracts (ACE) inhibit LPS or thioglycollate (TG)-induced inflammation by blocking the NF-κB signaling pathway in macrophages ( 174 ).…”
Section: The Action Mechanisms Of Phytochemicalsmentioning
confidence: 99%